The Effect of Government Expenditure on Education on the Enrollment Rate of Different Educational Levels in Selected OECD Countries (International Journal of Scientific Research and Management (IJSRM), 2023)
One of the most important factors in economic, social, and cultural development is to create a development plan to acquire knowledge, and govern the spirit of learning in the society, leading to the strengthening of human capital, and increasing the quality of the educational system in accordance with the needs of economic, and social development. Regarding this, and also based on the recognition of the importance of education in economic growth, economists, and economic development planners have paid special attention to the basics of resource allocation in the education sector. Therefore, according to the fact that government expenditure on education can be an effective factor to encourage people to acquire knowledge, and improve their level of education, and on the other hand, based on the fact that the improvement of people’s level of education in the society shows the increase of human capital in the country, which itself has a positive effect on the economic growth of the country, and the inequality reduction, this paper aims to investigate the effect of government expenditure on education on the enrollment rate in different educational levels in selected OECD countries from 2010 to 2019. The results show that the effect of all coefficients of the variables is expected based on the theoretical foundations, and the government expenditure on education has a significant positive effect on the enrollment rate in the primary, secondary, and tertiary levels.